Characterization and Genetic Analysis of a Novel Light-Dependent Lesion Mimic Mutant, lm3, Showing Adult-Plant Resistance to Powdery Mildew in Common Wheat - Wang, Fang (PLoS One, 2016)
Lesion mimics (LMs) that exhibit spontaneous disease-like lesions in the absence of pathogen attack might confer enhanced plant disease resistance to a wide range of pathogens. The LM mutant, lm3 was derived from a single naturally mutated individual in the F(1) population of a 3-1/Jing411 cross, backcrossed six times with 3–1 as the recurrent parent and subsequently self-pollinated twice. The leaves of young seedlings of the lm3 mutant exhibited small, discrete white lesions under natural field conditions. The lesions first appeared at the leaf tips and subsequently expanded throughout the entire leaf blade to the leaf sheath. The lesions were initiated through light intensity and day length. Histochemical staining revealed that lesion formation might reflect programmed cell death (PCD) and abnormal accumulation of reactive oxygen species (ROS). The chlorophyll content in the mutant was significantly lower than that in wildtype, and the ratio of chlorophyll a/b was increased significantly in the mutant compared with wildtype, indicating that lm3 showed impairment of the biosynthesis or degradation of chlorophyll, and that Chlorophyll b was prone to damage during lesion formation. The lm3 mutant exhibited enhanced resistance to wheat powdery mildew fungus (Blumeria graminis f. sp. tritici; Bgt) infection, which was consistent with the increased expression of seven pathogenesis-related (PR) and two wheat chemically induced (WCI) genes involved in the defense-related reaction. Genetic analysis showed that the mutation was controlled through a single partially dominant gene, which was closely linked to Xbarc203 on chromosome 3BL; this gene was delimited to a 40 Mb region between SSR3B450.37 and SSR3B492.6 using a large derived segregating population and the available Chinese Spring chromosome 3B genome sequence. Taken together, our results provide information regarding the identification of a novel wheat LM gene, which will facilitate the additional fine-mapping and cloning of the gene to understand the mechanism underlying LM initiation and disease resistance in common wheat.